Quantified CIN Score From Cell-free DNA as a Novel Noninvasive Predictor of Survival in Patients With Spinal Metastasis - Chen, Su; Yang, Minglei; Zhong, Nanzhe; Yu, Dong; Jian, Jiao; Jiang, Dongjie; Xiao, Yasong; Wei, Wei; Wang, Tianzhen; Lou, Yan; Zhou, Zhenhua; Xu, Wei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Purpose: Most currently available scores for survival prediction of patients with bone metastasis lack accuracy. In this study, we present a novel quantufied CIN (Chromosome Instability) score modeled from cfDNA CNV for survival prediction. Experimental Design: Plasma samples collected from 67 patients with bone metastases from 11 different cancer types between Nov 2015 and May 2016 were sent through low-coverage whole genome sequencing followed by CIN computation to make a correlation analysis between the CIN score and survival prognosis. The results were validated in an independent cohort of 213 patients. Results: During the median follow-up period of 598(95% confidence interval [CI]: 364-832) days till December 25th, 2018, 124 (44.3%) of the total 280 patients died. Analysis of the discovery dataset showed that CIN score=12 was the optimal CIN cutoff. Validation dataset showed that CIN was elevated (score≥12) in 87 (40.8%) patients, including 5 (5.75%) with head & neck cancer, 11 (12.6%) with liver & gallbladder cancer, 11 (12.6%) with cancer from unidentified sites, 21 (24.1%) with lung cancer, 7 (8.05%) with breast cancer, 4 (4.60%) with thyroid cancer, 6 (6.90%) with colorectal cancer, 4 (4.60%) with kidney cancer, 2 (2.30%) with prostate cancer and 16 (18.4%) with other types of cancer. Further analysis showed that patients with elevated CIN were associated with worse survival (p<0.001). For patients with low Tokuhashi score (≤8) who had the predictive survival less than 6 months, the CIN score was able to distinguish patients with a median OS of 443 days (95% CI: 301-585) from those with a median OS of 258 days (95% CI:184-332). Conclusions: CNV examination in bone metastatic cancer from cfDNA is superior to the traditional predictive model in that it provides a noninvasive and objective method of monitoring the survival of patients with spine metastasis.